2010
DOI: 10.4025/actasciagron.v32i4.8064
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic traits and seed yield produced in the soybean-corn crop in succession cropping

Abstract: Competition experiments were installed at the COODETEC unit in Palotina, Paraná State,, with the objective of evaluating the influence of the cultivation of soybean in succession to a second crop season on different sowing dates on the agronomic traits and seed yield in both cultures. The experiment consisted of four field replicates, arranged in a completely randomized block design and carried out in two agricultural years (2003/2004 and 2004/2005). The individual blocks were comprised of three early-maturing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…The practice of sowing early cultivars in this period has increased in order to prepare for the corn crop in succession planting. However, the results of the present study and those of Braccini et al (2010) indicate the need for caution in adopting this practice.…”
Section: Resultscontrasting
confidence: 42%
See 3 more Smart Citations
“…The practice of sowing early cultivars in this period has increased in order to prepare for the corn crop in succession planting. However, the results of the present study and those of Braccini et al (2010) indicate the need for caution in adopting this practice.…”
Section: Resultscontrasting
confidence: 42%
“…Since the BRS 360 RR cultivar belonged to maturity groups 6.0 and earlier, the crop sown in September had relatively low yield potential even when there was adequate water supply. Braccini et al (2010) reported that early cultivars sown during (1) p-value of the F-test.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this, research has been done in most of the principal soybean producing states in Brazil with the objective of comparing the quality of seed produced in later periods to that sowed conventionally (in October/ November) and, also, the productivity of different cultivars. Studies by Pereira et al (1979), Motta et al (2002), Ávila et al (2003), Dallacort et al (2008), Braccini et al (2010) in Paraná state; Paolinelli et al (1984) in Minas Gerais; Tragnago & Bonetti (1984) in Rio Grande do Sul; Nakagawa et al (1983Nakagawa et al ( , 1984Nakagawa et al ( , 1986 in São Paulo; Pereira et al (2000) in Goiás; Costa et al (1995) in Mato Grosso, evaluated both the quality and the productivity of soybean seed sown at different times (October to December), using different cultivars with groups having a distinct maturation (early, medium and latematuring varieties). Most of the authors cited previously mentioned that the seed quality of early-maturing cultivars, grown during the spring-summer period, is normally inferior to that of latematuring cultivars, grown during the same period.…”
Section: Quality and Productivity Of Soybean Seed Produced During Thementioning
confidence: 99%